The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa - Schawaller, Wolfgang (Zootaxa, 2019)
The species of Diaclina Jacquelin du Val, 1861 (Tenebrioninae: Alphitobiini) from the Sub-Saharan Africa are revised. Following new species are proposed: Diaclina ashantica sp. nov. (Ghana), D. grandis sp. nov. (Congo), D. muehlei sp. nov. (Rwanda). Diaclina ovalis Gebien, 1921 is revalidated. Following new synonyms are introduced: Diaclina gracilis (Fåhraeus, 1870) = Diaclina depressa Ardoin, 1963 syn. nov., Diaclina elliptica Ardoin, 1969 syn. nov.; Diaclina ovalis Gebien, 1921 = Diaclina decellei Ardoin, 1969 syn. nov. Lectotypes are designated for Diaclina brevicollis Gebien, 1921, D. cameruna Gebien, 1921, D. minuta Gebien, 1921, and D. ovalis Gebien, 1921. Habitus photographs and figures of aedeagi of all examined species are provided, and an identification key for the African species is added.